Timing of Maternal Immunization Affects Immunological and Behavioral Outcomes of Adult Offspring in Siberian Hamsters (Phodopus sungorus). Issue 6 (20th June 2016) - French, Susannah S.; Chester, Emily M.; Demas, Gregory E.
ABSTRACT: Maternal influences are an important contributing factor to offspring survival, development, and behavior. Common environmental pathogens can induce maternal immune responses and affect subsequent development of offspring. There are likely sensitive periods during pregnancy when animals are particularly vulnerable to environmental disruption. Here we characterize the effects of maternal immunization across pregnancy and postpartum on offspring physiology and behavior in Siberian hamsters ( Phodopus sungorus ). Hamsters were injected with the antigen keyhole limpet hemocyanin (KLH) (1) prior to pairing with a male (premating), (2) at separation (postmating), (3) at midpregnancy, or (4) after birth (lactation). Maternal food intake, body mass, and immunity were monitored throughout gestation, and litters were measured weekly for growth until adulthood when social behavior, hormone concentrations, and immune responses were determined. We found that immunizations altered maternal immunity throughout pregnancy and lactation. The effects of maternal treatment differed between male and female offspring. Aggressive behavior was enhanced in offspring of both sexes born to mothers treated postmating and thus early in pregnancy relative to other stages. In contrast, maternal treatment and maternal stage differentially affected innate immunity in males and females. Offspring cortisol, however, was unaffected by maternal treatment. Collectively, these data demonstrate that maternal immunization affects offspring physiology and behavior in a time‐dependent and sex‐specific manner. More broadly, these findings contribute to our understanding of the effects of maternal immune activation, whether it be from environmental exposure or immunization, on immunological and behavioral responses of offspring.